Experimental quantification of bulk sampling volume of ECH₂O soil moisture sensors - Limsuwat, Anuchit, author; Sakaki, Toshihiro, author; Illangasekare, Tissa H., author; Colorado State University, publisher (Colorado State University. Libraries, 2009)
Recently developed, relatively low cost, ECH2O soil moisture sensors have received considerable attention by both laboratory and field scientists. For these sensors to be installed properly, the sampling volume that defines the volume of soil zone where the soil moisture affects the sensor readings has to be known. These dielectric sensors comprise plus and ground prongs, where the sensitivity of the plus prong is higher than that of the ground prong. Moreover, the sensor head in which the circuitry is embedded has some sensitivity. It is not straightforward to incorporate these characteristics into numerical quantification of the sampling volume that is often used for conventional TDR probes. Therefore, we revisited a "classic" experimental approach for quantifying the bulk sampling volume of these sensors. We obtained sensor readings under varying distances between the sensor and a water-air interface, and determined the bulk sampling volume when the sensor readings start to show an "abrupt" change. Firstly, we tested two TDR probes (CS-640 and CS-630, Campbell Scientific, Inc.) and showed that the experimental procedure yielded results that were consistent with the previous findings. Secondly, we examined four ECH2O soil moisture sensors that differ in design (EC-5, TM, 5TE, and 10HS, Decagon Devices, Inc.). The results showed that: 1) the sensitivity of the plus prong was generally higher and the contribution of the ground prong varied depending on whether or not the ground prong was in air or under water, 2) abrupt changes were generally limited within small distances (order of ~1 to 2 cm) from the prongs, and 3) the sensor head affected the output readings by 35 % for EC-5, TM, and 10HS, and 34% for 5TE. Since the experiments were performed in air and under water, where soil moisture conditions are expected to be in between these extreme conditions, the estimated bulk sampling volumes should be valid in soils.
Hydrology days 2009
AGU hydrology days 2009
2009 annual AGU hydrology days was held at Colorado State University on March 25 - March 27, 2009.